Edukasi Pemanfaatan TOGA (Tanaman Obat Keluarga) Sebagai Produk Olahan Minuman Ramah Anak di MI Bilingual Al-Ikhlas - Isna Nurul Inayati; Melani Albar; Ana Nurwakhidah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The interest of the younger generation, especially elementary/MI age children, in consuming processed TOGA (Jamu) drinks is considered to be still very minimal. Children tend to think that herbal medicine is synonymous with a bitter taste and seems old-fashioned, so they are reluctant to consume it. For this reason, it is necessary to hold an educational process related to the use of TOGA to increase students' understanding of TOGA processed variants and increase the awareness of parents in using TOGA. The approaches and methods used in implementing this community service program are Appreciative Inquiry and Working Out Loud. The Appreciative Inquiry approach is used as an initial assessment in the field, while the Working Out Loud approach is education on the use of Toga as a processed child-friendly drink product at Mi Bilingual Al-Ikhlas. After the process has been carried out, the conclusions that can be drawn are 1) MI Bilingual Al-Ikhlas students have understood the types and functions of TOGA well. 2) The majority of MI Bilingual Al-Ikhlas students are interested and are no longer afraid of drinking JAMU because the preparation is comfortable to consume and has a positive impact on health